Functional diversity of soil nematodes in relation to the impact of agriculture - a review - Lazarova, S.; Coyne, D.; Rodríguez, G.; Peteira, B.; Ciancio, A. (MDPI, 2021)
The analysis of the functional diversity of soil nematodes requires detailed knowledge on theoretical aspects of the biodiversity–ecosystem functioning relationship in natural and managed terrestrial ecosystems. Basic approaches applied are reviewed, focusing on the impact and value of soil nematode diversity in crop production and on the most consistent external drivers affecting their stability. The role of nematode trophic guilds in two intensively cultivated crops are examined in more detail, as representative of agriculture from tropical/subtropical (banana) and temperate (apple) climates. The multiple facets of nematode network analysis, for management of multitrophic interactions and restoration purposes, represent complex tasks that require the integration of different interdisciplinary expertise. Understanding the evolutionary basis of nematode diversity at the field level, and its response to current changes, will help to explain the observed community shifts. Integrating approaches based on evolutionary biology, population genetics and ecology can quantify the contribution of nematode fauna to fundamental soil functions. These include carbon transformation, nutrient cycling, pest control and disease transmission. In conclusion, different facets of nematode diversity such as trophic groups, life history traits, variability in body size and/or taxa identities in combination with DNA-based techniques are needed in order to disclose nematode–soil–ecosystem functioning relationships. Further experimental studies are required to define locally adapted and sustainable management practices, through ecosystem-based approaches and nature-based solutions.